202 - ANALYSIS OF BODY POSTURE ADOPTED BY WOMEN WITH FIBROMYALGIA SYNDROME (Fiep Bulletin - online, 2011)
Introduction: Fibromyalgia is a chronic pain syndrome of unknown etiology that affects mainly women, is characterized by diffuse muscle pain and painful muscle points on palpation. Patients with the fibromyalgia syndrome (FMS) may also present: sleep disturbance, fatigue, chronic headaches, mental disorders, intestinal and functional. Many patients may have postural changes they see the influence negatively the quality of life and increase their pain complaints. Goal: To analyze the attitude that women with fibromyalgia syndrome. Methodological Approach: Sample consisted of 33 (thirty-three) women with fibromyalgia who participate in the interdisciplinary program at the physiotherapy clinic of UNIVALI. We analyzed the posture of each individual woman, as proposed by Marques (2005). The method of analysis was done by building a cross-reference table for comparison between means. Presentation and Discussion of Results: After assessing each woman with fibromyalgia syndrome, a predominantly static posture is as follows: standing with normal curvature, calcaneal valgus, knee valgus and external rotation, anterior tilting of the pelvis and uneven to the left, rotation of the pelvis to the right, lumbar spine with concavity is high and low is the normal curvature, normal thoracic kyphosis, large blades, shoulders bulged and uneven, clavicles in normal position, but with different depths, spine aligned, head tilted to the left and round to the right mandibular retraction. Closing Remarks: Postural changes found in women with fibromyalgia syndrome can be caused by several factors, as well as muscle imbalances, repetitive work, overload, fear, pain, sadness, anxiety, how does the life, anger and sense of abandonment.
Keywords: postural changes; physical therapy; fibromyalgia syndrome